U‐Pb and Hf isotope analysis of detrital zircons from Mesozoic strata of the Gravina belt, southeast Alaska. Issue 10 (3rd October 2015) - Yokelson, Intan; Gehrels, George E.; Pecha, Mark; Giesler, Dominique; White, Chelsi; McClelland, William C.
Abstract: The Gravina belt consists of Upper Jurassic through Lower Cretaceous marine clastic strata and mafic‐intermediate volcanic rocks that occur along the western flank of the Coast Mountains in southeast Alaska and coastal British Columbia. This report presents U‐Pb ages and Hf isotope determinations of detrital zircons that have been recovered from samples collected from various stratigraphic levels and from along the length of the belt. The results support previous interpretations that strata in the western portion of the Gravina belt accumulated along the inboard margin of the Alexander‐Wrangellia terrane and in a back‐arc position with respect to the western Coast Mountains batholith. Our results are also consistent with previous suggestions that eastern strata accumulated along the western margin of the inboard Stikine, Yukon‐Tanana, and Taku terranes and in a fore‐arc position with respect to the eastern Coast Mountains batholith. The history of juxtaposition of western and eastern assemblages is obscured by subsequent plutonism, deformation, and metamorphism within the Coast Mountains orogen, but may have occurred along an Early Cretaceous sinistral transform system. Our results are inconsistent with models in which an east‐facing subduction zone existed along the inboard margin of the Alexander‐Wrangellia terrane during Late Jurassic‐Early Cretaceous time. Key Points: Strata of the Gravina belt formed in two different sedimentary basins Western strata are related to the outboard Alexander and Wrangellia terranes Eastern strata formed outboard of the Yukon‐Tanana, Taku, and Stikine terranes